Cognitive and behavioral benefits of 2′-fucosyllactose in growing mice: the roles of 5-hydroxytryptophan and gut microbiota - Liuying Zhu; Zhiyi Zhang; Ting Luo; Hongyan Li; Zeyuan Deng; Jing Li; Liufeng Zheng; Jinqiang Liao; Minghui Wang; Bing Zhang (Microbiome)
Abstract Background 2′-Fucosyllactose (2′-FL) is one of the major oligosaccharides found in human breast milk, with several recognized beneficial effects on the host. Extensive research has indicated positive effects of 2′-FL on cognitive development in the brain, yet its molecular mechanisms have remained elusive. This study aimed to assess the impact of 2′-FL on the gut-brain axis microbiota and cognitive function in growing mice, along with its potential mechanisms of action. Results Following long-term supplementation for 4 weeks, 2′-FL was found to enhance cognitive memory function in growing mice (3 weeks old) as assessed through Y-maze, novel object recognition, and water maze tests. Analysis via 16S rRNA sequencing revealed significant alterations in gut microbiota diversity and composition induced by 2′-FL, notably increasing the relative abundance of Bacteroides and Lactobacillus genera. Additionally, 2′-FL significantly elevated levels of 5-hydroxytryptamine (5-HT) and 5-hydroxytryptophan (5-HTP) in the hippocampal tissue. However, antibiotic intervention abolished the cognitive advantage conferred by 2′-FL, highlighting the critical role of gut microbiota in mediating its effects. Similarly, short-term supplementation with 2′-FL for 7 days indicated rapid changes in gut microbiota composition preceding cognitive improvements, further suggesting a potential causal relationship between gut microbiota characteristics and cognition. Further, in vitro experiments with mouse feces suggested that 2′-FL may influence tryptophan hydroxylase levels in the gut microbiota and inhibit the activity of 5-hydroxytryptophan decarboxylase, potentially leading to increased accumulation of 5-HTP. Additionally, 2′-FL may indirectly impact tryptophan hydroxylase levels in enterochromaffin cells by promoting short-chain fatty acid production, which could support 5-HTP synthesis. Elevated 5-HTP produced by the gut system enters the bloodstream, crosses the blood–brain barrier, and may potentially enhance brain 5-HT levels. Conclusion This study offers preliminary evidence that the cognitive-promoting effects of 2′-FL in mice may be closely associated with gut microbiota and 5-HT. The findings suggest that 2′-FL contribute to cognitive development in growing mice, potentially by modulating gut microbiota and enhancing 5-HT levels in the brain. Video Abstract